Transformation of Residential Space as an Adaptation Process during the COVID-19 Pandemic - Anisa Anisa; Finta Lissimia; Ratna Dewi Nur'aini; Ashadi Ashadi; Munirah Radin Mohd Mokhtar (Department of Architecture Universitas Muhammadiyah Jakarta, 2021)
A residence is a place to live that accommodates daily activities. Under normal conditions, housing is used as a place to unwind after work and school outside the home. Since December 2019 major changes have taken place globally that have an impact on housing. This change was due to the rapid spread of the COVID-19 virus and reached various regions. Changes due to the spread of the Covid-19 virus have caused changes in the order of life because all activities that were initially carried out outside the home, have shifted to being carried out indoors. This happens because to reduce the impact of the spread of the virus, humans must practice social distancing. The biggest change that occurred was the shift from formal school activities and work to housing. With the addition of this activity, the residence must be able to be used functionally and meet comfort for the smooth running of activities in it. The purpose of this study is to identify, describe, and interpret changes in the function of space in residential areas as an adaptation process during a pandemic. The research method used is qualitative with purposive sampling. This qualitative research was conducted inductively by observing and interviewing the research case. Data were taken purposively on 6 residential areas in Jakarta, Depok, Bogor, Tangerang, and Bekasi. The results of this study are changes that occur in residential spaces in the form of non-physical changes, namely by adding activities that are accommodated in the space. Physically the space has not changed, this shows that the non-physical changes that occur are an adaptation process carried out by residential users. The adaptation process that occurs begins with adjusting activities to the available space in the dwelling. In the process of adaptation that occurs will choose a room that has the character as the need for new activities during the pandemic. In the end, housing can provide a positive response to the COVID-19 pandemic with flexibility in the use of space to accommodate new functions.